Marketing e Luz/Cor - Estruturação do Espaço Cultural - Fernandes, Simone (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1996)
This article intend to explain some aspects about Visual Communication and your marketing implications,connecting light/color of environment with supermarket atmosphere. To make part of analysis, as marketing strategy of light/color, the product place into supermarket, color package, ilumination, like as, all objects that making environm ent identity of comercial space